Chemical engineering design - Towler, Gavin P.; Sinnott, R. K. (Oxford : Butterworth-Heinemann, 2009)
Featuring case studies and worked examples that illustrate key concepts in the text, this book contains guidelines for scaleup of laboratory and pilot plant results, methods to derive the correct reaction order, activation energy, or kinetic model from laboratory tests, and theories, correlations, and practical examples for 2- and 3-phase reaction systems, including bubble columns, slurry reactions, trickle-led reactors, and fluidized beds. A comprehensive reference, the book offers strategies to analyze and interpret kinetic data for homogeneous and heterogeneous reactions, practical design procedures, rate equations, and analytical models for improved reactor performance.
Introduction to design -- Fundamentals of material balances -- Fundamentals of energy balances (and energy utilisation) -- Flow-sheeting -- Piping and instrumentation -- Costing and project evaluation -- Materials of construction -- Design information and data -- Safety and loss prevention -- Equipment selection, specification and design -- Separation columns (distillation, absorption and extraction) -- Heat-transfer equipment; Mechanical design of process equipment; General site considerations -- Appendices -- Full solutions manual online -- accompanying design and flowsheeting software tools -- plus costing templates and data sources for downloading -- complete set of figures in PowerPoint format for lecture slide download by instructors.
Includes bibliographical references and index.
1
Keywords: Chemical engineering